Porous Co2VO4 Nanodisk as a High-Energy and Fast-Charging Anode for Lithium-Ion Batteries - Ren, Jinghui; Wang, Zhenyu; Xu, Peng; Wang, Cong; Gao, Fei; Zhao, Decheng; Liu, Shupei; Yang, Han; Wang, Di; Niu, Chunming; Zhu, Yusong; Wu, Yutong; et al. (Nano-Micro Letters, 2021)
High-energy–density lithium-ion batteries (LIBs) that can be safely fast-charged are desirable for electric vehicles. However, sub-optimal lithiation potential and low capacity of commonly used LIBs anode cause safety issues and low energy density. Here we hypothesize that a cobalt vanadate oxide, Co2VO4, can be attractive anode material for fast-charging LIBs due to its high capacity ( 1000 mAh g−1) and safe lithiation potential ( 0.65 V vs. Li+/Li). The Li+ diffusion coefficient of Co2VO4 is evaluated by theoretical calculation to be as high as 3.15 × 10–10 cm2 s−1, proving Co2VO4 a promising anode in fast-charging LIBs. A hexagonal porous Co2VO4 nanodisk (PCVO ND) structure is designed accordingly, featuring a high specific surface area of 74.57 m2 g−1 and numerous pores with a pore size of 14 nm. This unique structure succeeds in enhancing Li+ and electron transfer, leading to superior fast-charging performance than current commercial anodes. As a result, the PCVO ND shows a high initial reversible capacity of 911.0 mAh g−1 at 0.4 C, excellent fast-charging capacity (344.3 mAh g−1 at 10 C for 1000 cycles), outstanding long-term cycling stability (only 0.024% capacity loss per cycle at 10 C for 1000 cycles), confirming the commercial feasibility of PCVO ND in fast-charging LIBs. Highlights: 1 The Li+ diffusion coefficient of Co2VO4 is evaluated by theoretical calculation to be as high as 3.15 × 10–10 cm2 s−1, theoretically proving Co2VO4 a promising anode in fast-charging lithium-ion batteries. 2 A hexagonal porous Co2VO4 nanodisk (PCVO ND) structure is designed, featuring a high specific surface area of 74.57 m2 g−1 and numerous pores with a pore size of 14 nm. 3 The PCVO ND shows excellent fast-charging performance (a high average capacity of 344.3 mAh g−1 at 10 C for 1000 cycles with only 0.024% capacity loss per cycle for 1000 cycles).